SIZE AND OPTIC CHARACTERISTICS OF METAL OXIDE NANOPARTICLES OBTAINED BY ACOUSTOPLASMA TECHNIQUE - Dorokhov, Victor; Hauser, Yulia (Revista Inclusiones, 2020)
Nanoparticles of tungsten, copper, iron, and zinc oxides were synthesized in acoustoplasma discharge. Their size distribution was studied by electron microscopy and laser correlation spectroscopy. Water suspensions of zinc oxide nanoparticles showed photoluminescence in red and near infrared spectral ranges, which makes them a promising material for luminescent diagnostics of biological systems.